Beautiful bookbindings a thousand years of the bookbinder's art - Marks, P. J. M. (British Library, 2011)
"Visual overview of 100 bookbindings designed in the last thousand years, examining the history and technique of the craft. Includes work by binders Mearne, Padeloup, Payne, Simier, and others. Illustrated with color photographs from The British Library"--Provided by publisher.